2021
DOI: 10.1038/s41598-021-89054-1
|View full text |Cite
|
Sign up to set email alerts
|

Monotonous driving induces shifts in spatial attention as a function of handedness

Abstract: Current evidence suggests that the ability to detect and react to information under lowered alertness conditions might be more impaired on the left than the right side of space. This evidence derives mainly from right-handers being assessed in computer and paper-and-pencil spatial attention tasks. However, there are suggestions that left-handers might show impairments on the opposite (right) side compared to right-handers with lowered alertness, and it is unclear whether the impairments observed in the compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The results of the study showed that decreases in the frequency of shifting spatial attentions increased the change in heart rate, had no effect on the change of blood pressure, and increased pupillary dilations across the participants in the study. A potential explanation for the results are that when the participants looked at a point for longer periods of time, mental strain and focus were likely to increase [1]. Therefore, SNS activity would increase, resulting in the measures found throughout the study.…”
Section: Discussionmentioning
confidence: 95%
“…The results of the study showed that decreases in the frequency of shifting spatial attentions increased the change in heart rate, had no effect on the change of blood pressure, and increased pupillary dilations across the participants in the study. A potential explanation for the results are that when the participants looked at a point for longer periods of time, mental strain and focus were likely to increase [1]. Therefore, SNS activity would increase, resulting in the measures found throughout the study.…”
Section: Discussionmentioning
confidence: 95%